Corporate Governance in Mexico - Husted, Bryan W. (Journal of business ethics, 2002)
This paper looks broadly at the theme of corporate governance in Mexico. It begins with a brief analysis of the historical corporate governance model in Mexico, including the governance structures, the banking and financial systems, ownership and control patterns, industrial policy, and industrial relations. The paper then examines how and why these various aspects of corporate governance have been changing with processes of economic liberalization currently under way. Finally, it analyzes the consequences of changes in the model of corporate governance for the country's development (e.g. increased consumer goods for middle class consumers, increased disclosure by domestic corporations, less support for corporate social programs, etc.).